Method for improving loading capacity of honeycomb-shaped catalytic carrier and preparation of denitration catalyst based on honeycomb-shaped catalytic carrier
By adjusting the honeycomb catalytic support structure, using alkali etching and water-soluble treatment technology to broaden the inner wall channels, the problem of disconnection of the inner wall of the support is solved, the adhesion rate and catalytic activity of the coating slurry are improved, and the high Preparation of a supported molecular sieve-based coated honeycomb integrated denitrification catalyst.
Patent Information
- Application Number
- CN202411531011.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, the inner wall of the honeycomb catalytic support is not connected, making it difficult to adhere to the coating slurry, and hole blockage and slurry hanging are prone to occur, which limits the load capacity and catalytic activity of the catalyst.
Use natural silicon-aluminum minerals to mix with structural manufacturing agents (such as water-soluble polymer bundled fibers), and after alkali erosion and structured water-soluble treatment, the inner wall channels are widened, the contact time and contact area of the coating slurry are increased, and the hole blockage is reduced. Phenomenon, a high-loaded molecular sieve-based coated honeycomb integrated denitrification catalyst was prepared.
It effectively improves the load capacity and catalytic activity of the catalyst, reduces the phenomenon of hole blockage and slurry hanging, and has good industrial application prospects.
Smart Images

Figure CN119186545A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nitrogen oxide removal, and particularly relates to a method for increasing the loading amount of a honeycomb catalytic carrier and the preparation of a denitration catalyst based on the catalytic carrier. Background Art
[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, which is extremely harmful to human body, environment and even social economy. Among the many denitrification technologies, the selective catalytic reduction (NH3-SCR) technology using ammonia as a reducing agent is the most mature and widely used.
[0003] In practical applications, honeycomb monolithic catalysts are mostly used. For coated molecular sieve-based honeycomb monolithic catalysts, they have obvious advantages: 1. The amount of sieve catalyst used is small, which can save a lot of production costs; 2. It can effectively replace traditional V-based catalysts and reduce biological toxicity. 3. The active site exposure rate is high and the active accessibility is high. However, due to the barren nature of molecular sieve catalysts, it is difficult to attach, and increasing its effective loading amount has become a huge problem.
[0004] Chinese patent CN 108889295B uses electromagnetic oscillation dispersion method to develop a coating technology for high-viscosity catalytic slurry, which effectively improves the dispersion of SCR coating slurry, increases the loading amount, and reduces the shedding rate and pore blocking rate. However, its oscillation method still has certain difficulties in industrial application and is difficult to apply on a large scale. Chinese patent CN 107597178B starts with coating slurry and uses α-Al2O3 as a binder to achieve effective loading of molecular sieve catalysts, with a loading amount of 1 to 10%, and a shedding rate of less than 20%, which improves the catalytic performance to a certain extent. Chinese patent application CN 106268929A combines Al sol and Si sol to improve slurry stability, reduce pore blocking and slurry hanging phenomena, and promote the coating application of molecular sieve catalysts. In this type of technology, although the coating slurry has a certain improvement, the total loading amount of the coating slurry on the carrier has reached saturation and is difficult to continue to increase, so the catalyst carrier needs to be modified to a certain extent.
[0005] Chinese patent CN 115417694B soaks and cooks the carrier in a nitric acid solution, and then washes it with water to obtain a honeycomb integral adsorbent. Chinese patent application CN 107349968 A soaks the honeycomb carrier in an organic solvent to obtain an SCR molecular sieve honeycomb catalyst. Chinese patent CN 116023126B uses pore-making technology to increase the porosity of the honeycomb and create micropores so that the coating slurry can enter the internal channels. The above technology illustrates the possibility of modifying the honeycomb carrier. Pretreatment of the honeycomb catalytic carrier can increase the surface roughness and porosity, and increase the loading capacity of the slurry to a certain extent. However, since this type of technology only performs microscopic treatment on the surface of the carrier, it cannot effectively load the complex conditions of the slurry, and is prone to pore blockage and slurry hanging. Summary of the invention
[0006] The purpose of the present invention is to provide a method for increasing the loading of a honeycomb catalytic carrier and the preparation of a denitration catalyst based on the catalytic carrier. Specifically, the present invention provides a method for increasing the loading of a clay-based honeycomb catalytic carrier and a method for preparing a high-load molecular sieve-based coated honeycomb monolithic denitration catalyst, which aims to solve the problem of the inner wall of the honeycomb catalytic carrier being disconnected, and to effectively widen the inner wall channel by structurally adjusting the honeycomb catalytic carrier, thereby increasing the contact time and contact area of the molecular sieve-based coated slurry during the subsequent preparation of the denitration catalyst, overcoming the problem of the slurry being difficult to adhere to, reducing the pore blocking phenomenon and the slurry hanging phenomenon, and thus increasing the slurry loading rate of the catalyst and improving its catalytic activity.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention first provides a method for increasing the loading capacity of a clay-based honeycomb catalytic carrier, comprising the following steps:
[0009] (1) Taking natural silicon-aluminum mineral as the main body, adding a structure-making agent and an auxiliary agent, and mixing to obtain a uniform powder; adding wet material, kneading, slurrying, aging, pre-extrusion, extrusion molding, and pre-drying to obtain a clay-based honeycomb monolithic denitrification catalytic carrier;
[0010] (2) soaking the above catalyst support in an alkali solution for etching: the pH of the alkali solution is 8 to 13, the temperature is 20 to 90° C., and the soaking time is 2 to 4 hours;
[0011] (3) Then the catalyst carrier is subjected to a structured water-soluble treatment: the catalyst carrier is immersed in water at 20 to 90° C. for 0.5 to 2.0 h, and then rinsed with water at 20 to 90° C. for 2 to 3 times (the water temperature in this step is set according to the dissolution temperature of the structure-making agent);
[0012] (4) Finally, the catalyst carrier is dried and calcined to obtain a structured clay-based honeycomb catalyst carrier.
[0013] The natural silica-aluminum mineral is one or more of feldspar, nepheline, leucite, beryl, muscovite, pyrophyllite, kaolinite, rectorite, jadeite, spodumene, diaspore, perlite, phlogopite, vermiculite, montmorillonite, talc, serpentine, illite, palygorskite, sepiolite, diatomaceous earth, attapulgite, enstatite, diopside, amphibole, and olivine, wherein the impurity content (substances other than alumina and silicon dioxide) of the natural silica-aluminum mineral is less than 20wt%, and the particle size is not less than 200 meshes.
[0014] The structure manufacturing agent is a water-soluble polymer bundle fiber, including one or more of polyvinyl alcohol fiber, seaweed fiber, and carboxymethyl cellulose fiber. It is required to be in the form of strips. Specifically, the length is required to be 0.2mm to 3.0mm, and the diameter is required to be 10μm to 2000μm. The length is adjusted according to the thickness of the honeycomb wall to achieve the purpose of directly penetrating the inner wall.
[0015] The auxiliary agent is an organic binder, an extrusion aid, a pore former, and a structural reinforcing agent. Further, the organic binder is one or more of sodium carboxymethyl cellulose, sodium hydroxypropyl cellulose, polyethylene glycol, sodium polyacrylate, polyethylene oxide, and phenolic resin; the extrusion aid is one or more of starch, sesbania powder, ethanolamine, and sodium stearate; the pore former is one or more of straw, rice husk, sawdust, wood chips, and bamboo chips, with a particle size of not less than 200 meshes; the structural reinforcing agent is glass fiber, with a length requirement of 1.0 to 10.0 mm.
[0016] The wet materials are inorganic binder, organic acid, inorganic acid, humectant and water.
[0017] Furthermore, the inorganic binder is one or more of silica sol, water glass, pseudo-boehmite, and aluminum sol; the organic acid is one or more of citric acid, tartaric acid, malic acid, oxalic acid, and lactic acid; the inorganic acid is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, carbonic acid, and boric acid. The concentrations of the organic acid aqueous solution and the inorganic acid aqueous solution are both 3 to 20 wt%. The moisturizer is one or more of glycerin, tung oil, and peanut oil; the water is one or more of deionized water, pure water, and mineral water.
[0018] Furthermore, the mass ratio of each raw material added is: natural silica-alumina mineral: organic binder: extrusion aid: structure enhancer: structure manufacturing agent: pore former: inorganic binder: organic acid: inorganic acid: humectant: water = 45~100:1~5:1~8:1~5:10~50:1~15:3~8:1~5:1~5:3~10:10~30.
[0019] In step (1), the dry material mixing time is 10 to 60 minutes; the kneading is stirring after all the dry materials and wet materials are added, and the mixing time is 10 to 60 minutes; the number of times of mud kneading is 2 to 3 times; the aging time is 1 to 10 days; the pre-extrusion is trial extrusion and mold lubrication after replacing the mold, and the pre-extrusion time is 5 to 30 minutes; the extrusion molding is twin-screw extrusion, and extrusion molding is carried out in conjunction with molds of different shapes, and the wall thickness adjustment range is 0.5 to 3.0 mm; the pre-drying is pre-removing 5wt% of the moisture of the entire extruded material.
[0020] The drying method described in step (4) is a temperature and humidity coordinated cross control method, that is, the humidity and temperature curves are controlled to cross each other, and the drying and dehydration are coordinated, the temperature is 25-100°C, and the humidity is 5%-80%. The calcination method described in step (4) adopts a low-rate platform heating method, and the calcination is carried out in a closed muffle furnace, the starting temperature is>80oC, the heating rate is 0.5-2°C / min, and the temperature is 80-800°C; during the calcination process, a platform is set at 180-400°C for calcination and debinding, and then the temperature is continued to be raised to 550-800°C for calcination for 6-8h.
[0021] The present invention also provides a method for preparing a high-load molecular sieve-based coated honeycomb monolithic denitration catalyst, comprising the following steps:
[0022] a) mixing molecular sieve, organic binder, inorganic binder, acid and water in a mass ratio of 10-30:0-10:0-10:3-10:50-90 to obtain a molecular sieve-based coating slurry;
[0023] b) completely immersing the structured clay-based honeycomb catalyst carrier obtained in the above step 4) in the molecular sieve-based coating slurry for 4 to 8 hours, blowing it with compressed air (4 bar) until no liquid drops, drying it at 80 to 100° C., and then immersing it in the molecular sieve-based coating slurry again for 4 to 8 hours, blowing it with compressed air until no liquid drops, and drying it at 80 to 100° C.;
[0024] c) Finally, the material is calcined at 500-600° C. to obtain a high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst, which can be applied to NH3-SCR reaction.
[0025] The mass m1 was weighed before dipping, and the mass m2 was weighed after the second dipping and drying. The load factor L was calculated as L = (m2-m1) / m1×100%.
[0026] The molecular sieve described in step a) is one or more of ZSM-5 molecular sieve, ZSM-35 molecular sieve, SSZ-13 molecular sieve, SSZ-39 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-47 molecular sieve, Y-type molecular sieve, Beta molecular sieve, KFI type molecular sieve, and mordenite (MOR), and the molar ratio of silicon dioxide to aluminum oxide of the molecular sieve is 2 to 300:1; the metal element contained in the molecular sieve is one or more of iron, copper, manganese, cerium, lanthanum, rhodium, ruthenium, palladium, and osmium, and the content of the metal element is 0.1 to 10.0wt%.
[0027] The organic binder in step a) is one or more of sodium carboxymethyl cellulose, polyethylene glycol, polyethylene oxide, sodium polyacrylate, and polyimide resin; the inorganic binder is silica sol or aluminum sol; the acid is one or more of lactic acid, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, carbonic acid, and boric acid; the water is one or more of deionized water, pure water, and mineral water.
[0028] The present invention adopts the above technical solution, adopts a two-step pretreatment method of alkali solution etching and structured water dissolution in the preparation process of the catalytic carrier, and manufactures connecting channels between the inner walls, which has high connectivity. Subsequently, the molecular sieve-based coating technology is adopted, and the high-connectivity carrier can reduce the internal pore blockage and slurry hanging phenomenon, and a high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst can be prepared.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] The present invention adopts natural silica-aluminum minerals and a structural manufacturing agent (polymer water-soluble bundled fibers) to prepare a catalytic carrier, and utilizes the characteristics of alkaline solution corrosion of natural silica-aluminum minerals to effectively control the surface roughness, retain the Al acidic sites in the natural silica-aluminum minerals, and increase the adsorption capacity; utilizes the water-soluble characteristics of the polymer water-soluble bundled fibers to effectively increase the degree of penetration of the inner wall, increase the slurry contact channel, and reduce pore blockage and slurry hanging phenomena.
[0031] The technology of the present invention carries out structural adjustment on the honeycomb catalyst carrier and adopts a two-step pretreatment technology to effectively increase the loading amount of the catalytic slurry, which is beneficial to the loading of the subsequent molecular sieve-based coating slurry and reduces pore blockage and shedding phenomena, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a comparison chart of the activities of the catalysts prepared in Example 1 and Example 4. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific examples, which are intended to illustrate the implementation scheme and features of the present invention in detail and should not be construed as any limitation to the present invention.
[0034] The FeCu-ZSM-5, FeCu-SSZ-13 and FeCu-SAPO-34 molecular sieves in the examples are high-performance denitrification molecular sieves synthesized in situ by a one-pot method, and belong to bimetallic molecular sieve catalysts. The introduction of Cu can not only regulate the Fe 3+ and the acidity of molecular sieves, and can also improve their redox ability and isolate Cu 2+ , higher framework Fe 3+ , good redox properties and acidic molecular sieve catalyst has good denitration catalytic activity Example 1
[0035] 1. Method for increasing the loading capacity of honeycomb catalyst carrier
[0036] The following raw materials were weighed in parts by mass: 45 parts of natural silica-alumina mineral kaolin, 3 parts of sodium carboxymethyl cellulose, 5 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 20 parts of water-soluble polyvinyl alcohol bundle fibers, 10 parts of sawdust, 7 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 10 parts of glycerol, and 25 parts of deionized water.
[0037] (1) adding natural silica-alumina mineral kaolin, sodium carboxymethyl cellulose, sesbania powder, glass fiber, and sawdust into a mixer and mixing them uniformly to obtain a uniform dry material;
[0038] (2) adding water-soluble polyvinyl alcohol bundle fibers and mixing evenly;
[0039] (3) adding silica sol, lactic acid, nitric acid, glycerin and deionized water and kneading;
[0040] (4) repeatedly kneading the clay material kneaded in step (3) for 2 to 3 times;
[0041] (5) Seal the clay material in step (4) with plastic wrap and place it in a dry and cool place for aging for 48 hours;
[0042] (6) placing the clay material prepared in step (5) into a molding machine for extrusion molding;
[0043] (7) The formed honeycomb was pre-dried, 5 wt% of the total mass of water was removed, and the honeycomb was placed in an alkaline solution (NaOH solution) with a pH of 10 and soaked for 2 hours. After being taken out, the honeycomb was placed in 60°C water to remove the water-soluble polyvinyl alcohol bundle fibers, and after being soaked for 10 hours, the honeycomb was taken out and rinsed with 70°C water for 3 times to obtain material A.
[0044] (8) Material A is dried, and its drying curve is: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally, it is transferred to a common oven at 100°C and dried for 3 hours to obtain material B.
[0045] (9) Material B is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 200°C for debinding for 2 hours, the temperature is further increased to 400°C and maintained for 2 hours, and then the temperature is increased to 600°C and maintained for 8 hours to obtain a structured honeycomb catalytic carrier.
[0046] 2. Preparation of denitration catalyst based on the above catalytic carrier
[0047] (1) Take 25 parts of FeCu-ZSM-5 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 2 parts of lactic acid, 2 parts of silica sol, and 116 parts of deionized water, and mix them evenly to obtain a molecular sieve-based coating slurry.
[0048] (2) Weigh the structured honeycomb catalyst carrier, record it as m1, m1 = 61.31 g, and immerse it completely in the coating slurry for 4 hours. After taking it out, blow it with compressed air (4 bar) until no liquid drops fall to ensure the honeycomb permeability, and then dry it at 100°C for 8 hours to obtain sample A.
[0049] (3) Sample A was completely immersed in the coating slurry for 4 hours. After being taken out, it was purged with compressed air (4 bar) until no liquid droplets fell to ensure the honeycomb permeability. It was then dried at 100° C. for 8 hours to obtain sample B.
[0050] The sample was weighed and recorded as m2, m2 = 71.58 g. According to the load formula, L = (m2-m1) / m1×100%, L = 16.75%.
[0051] (4) Sample B was placed in a muffle furnace and heated to 600° C. for calcination for 5 h at a heating rate of 2° C. / min to obtain a highly loaded molecular sieve-based coated honeycomb monolithic denitrification catalyst.
[0052] The prepared high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst was placed in the monolithic catalyst evaluation device to simulate the flue gas components N2, H2O, NO, NH3, and O2 for evaluation, maintaining the air velocity at 5000h -1 , [NO] = [NH3] = 500ppm, [O2] = 5%, H2O = 5%, respectively detect the NO concentration at the inlet and outlet, calculate the denitration efficiency of the catalyst, and the activity evaluation results are shown in Figure 1 .
[0053] Example 2
[0054] 1. Method for increasing the loading capacity of honeycomb catalyst carrier
[0055] The following raw materials were weighed in parts by mass: 37 parts of natural silica-alumina mineral kaolin, 3 parts of sodium carboxymethyl cellulose, 5 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 20 parts of water-soluble polyvinyl alcohol bundle fibers, 10 parts of sawdust, 7 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 10 parts of glycerol, and 25 parts of deionized water.
[0056] (1) adding natural silica-alumina mineral kaolin, sodium carboxymethyl cellulose, sesbania powder, glass fiber, and sawdust into a mixer and mixing them uniformly to obtain a uniform dry material;
[0057] (2) adding water-soluble polyvinyl alcohol bundle fibers and mixing evenly;
[0058] (3) adding silica sol, lactic acid, nitric acid, glycerin and deionized water and kneading;
[0059] (4) repeatedly kneading the clay material kneaded in step (3) for 2 to 3 times;
[0060] (5) Seal the clay material in step (4) with plastic wrap and place it in a dry and cool place for aging for 48 hours;
[0061] (6) placing the clay material prepared in step (5) into a molding machine for extrusion molding;
[0062] (7) The formed honeycomb was pre-dried, 5 wt% of the total mass of water was removed, and the honeycomb was placed in an alkaline solution (NaOH solution) with a pH of 10 and soaked for 2 hours. After being taken out, the honeycomb was placed in 60°C water to remove the water-soluble polyvinyl alcohol bundle fibers, and after being soaked for 10 hours, the honeycomb was taken out and rinsed with 70°C water for 3 times to obtain material A.
[0063] (8) Material A is dried, and its drying curve is: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally, it is transferred to a common oven at 100°C and dried for 3 hours to obtain material B.
[0064] (9) Material B is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 200°C for debinding for 2 hours, the temperature is further increased to 400°C and maintained for 2 hours, and then the temperature is increased to 600°C and maintained for 8 hours to obtain a structured honeycomb catalytic carrier.
[0065] 2. Preparation of denitration catalyst based on the above catalytic carrier
[0066] (1) Take 25 parts of FeCu-ZSM-5 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 8 parts of aluminum sol, 2 parts of lactic acid, and 116 parts of deionized water, and mix them evenly to obtain a molecular sieve-based coating slurry.
[0067] (2) Weigh the structured honeycomb catalyst carrier, record it as m1, m1 = 67.46 g, and immerse it completely in the coating slurry for 4 hours. After taking it out, blow it with compressed air (4 bar) until no liquid drops fall to ensure the honeycomb permeability, and then dry it at 100°C for 8 hours to obtain sample A.
[0068] (3) Sample A was completely immersed in the coating slurry for 4 hours. After being taken out, it was purged with compressed air (4 bar) until no liquid droplets fell to ensure the honeycomb permeability. It was then dried at 100° C. for 8 hours to obtain sample B.
[0069] The sample was weighed and recorded as m2, m2 = 82.81 g. According to the load formula, L = (m2-m1) / m1×100%, L = 22.75%.
[0070] (4) Sample B was placed in a muffle furnace and heated to 600° C. for calcination for 5 h at a heating rate of 2° C. / min to obtain a highly loaded molecular sieve-based coated honeycomb monolithic denitrification catalyst.
[0071] The prepared high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst was placed in the monolithic catalyst evaluation device to simulate the flue gas components N2, H2O, NO, NH3, and O2 for evaluation, maintaining the air velocity at 5000h -1 , [NO] = [NH3] = 500ppm, [O2] = 5%, H2O = 5%, detect the NO concentration at the inlet and outlet respectively, and calculate the denitrification efficiency of the catalyst.
[0072] Example 3
[0073] 1. Method for increasing the loading capacity of honeycomb catalyst carrier
[0074] The following raw materials were weighed in parts by mass: 34 parts of natural silica-alumina mineral kaolin, 3 parts of sodium carboxymethyl cellulose, 5 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 20 parts of water-soluble polyvinyl alcohol bundle fibers, 10 parts of sawdust, 7 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 10 parts of glycerol, and 25 parts of deionized water.
[0075] (1) adding natural silica-alumina mineral kaolin, sodium carboxymethyl cellulose, sesbania powder, glass fiber, and sawdust into a mixer and mixing them uniformly to obtain a uniform dry material;
[0076] (2) adding water-soluble polyvinyl alcohol bundle fibers and mixing evenly;
[0077] (3) adding silica sol, lactic acid, nitric acid, glycerin and deionized water and kneading;
[0078] (4) repeatedly kneading the clay material kneaded in step (3) for 2 to 3 times;
[0079] (5) Seal the clay material in step (4) with plastic wrap and place it in a dry and cool place for aging for 48 hours;
[0080] (6) placing the clay material prepared in step (5) into a molding machine for extrusion molding;
[0081] (7) The formed honeycomb was pre-dried, 5 wt% of the total mass of water was removed, and the honeycomb was placed in an alkaline solution (NaOH solution) with a pH of 10 and soaked for 2 hours. After being taken out, the honeycomb was placed in 60°C water to remove the water-soluble polyvinyl alcohol bundle fibers, and after being soaked for 10 hours, the honeycomb was taken out and rinsed with 70°C water for 3 times to obtain material A.
[0082] (8) Material A is dried, and its drying curve is: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally, it is transferred to a common oven at 100°C and dried for 3 hours to obtain material B.
[0083] (9) Material B is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 200°C for debinding for 2 hours, the temperature is further increased to 400°C and maintained for 2 hours, and then the temperature is increased to 600°C and maintained for 8 hours to obtain a structured honeycomb catalytic carrier.
[0084] 2. Preparation of denitration catalyst based on the above catalytic carrier
[0085] (1) Take 25 parts of FeCu-ZSM-5 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 10 parts of aluminum sol, 2 parts of lactic acid, and 116 parts of deionized water, and mix them evenly to obtain a molecular sieve-based coating slurry.
[0086] (2) Weigh the structured honeycomb catalyst carrier, record it as m1, m1 = 61.31 g, and immerse it completely in the coating slurry for 4 hours. After taking it out, blow it with compressed air (4 bar) until no liquid drops fall to ensure the honeycomb permeability, and then dry it at 100°C for 8 hours to obtain sample A.
[0087] (3) Sample A was completely immersed in the coating slurry for 4 hours. After being taken out, it was purged with compressed air (4 bar) until no liquid droplets fell to ensure the honeycomb permeability. It was then dried at 100° C. for 8 hours to obtain sample B.
[0088] The sample was weighed and recorded as m2, m2 = 80.31 g. According to the load formula, L = (m2-m1) / m1×100%, L = 24.76%.
[0089] (4) Sample B was placed in a muffle furnace and heated to 600° C. for calcination for 5 h at a heating rate of 2° C. / min to obtain a highly loaded molecular sieve-based coated honeycomb monolithic denitrification catalyst.
[0090] The prepared high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst was placed in the monolithic catalyst evaluation device to simulate the flue gas components N2, H2O, NO, NH3, and O2 for evaluation, maintaining the air velocity at 5000h -1 , [NO] = [NH3] = 500ppm, [O2] = 5%, H2O = 5%, detect the NO concentration at the inlet and outlet respectively, and calculate the denitrification efficiency of the catalyst.
[0091] Example 4
[0092] 1. Method for increasing the loading capacity of honeycomb catalyst carrier
[0093] The following raw materials were weighed in parts by mass: 50 parts of natural silica-alumina mineral kaolin, 3 parts of sodium carboxymethyl cellulose, 5 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 10 parts of sawdust, 7 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 10 parts of glycerol, and 25 parts of deionized water.
[0094] (1) adding natural silica-alumina mineral kaolin, sodium carboxymethyl cellulose, sesbania powder, glass fiber, and sawdust into a mixer and mixing them uniformly to obtain a uniform dry material;
[0095] (2) adding silica sol, lactic acid, nitric acid, glycerin and deionized water and kneading;
[0096] (3) Knead the kneaded clay material repeatedly for 2 to 3 times;
[0097] (4) Seal the mud material in step (3) with plastic wrap and place it in a dry and cool place for aging for 48 hours;
[0098] (5) placing the clay material prepared in step (4) into a molding machine for extrusion molding;
[0099] (6) The formed honeycomb was pre-dried, 5 wt% of the total mass of water was removed, and the honeycomb was placed in an alkaline solution (NaOH solution) with a pH of 10 and soaked for 2 hours. After being taken out, the honeycomb was placed in 60°C water to remove the water-soluble polyvinyl alcohol bundle fibers, and after being soaked for 10 hours, the honeycomb was taken out and rinsed with 70°C water for 3 times to obtain material A.
[0100] (7) Material A is dried, and its drying curve is: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally, it is transferred to a common oven at 100°C and dried for 3 hours to obtain material B.
[0101] (8) Material B is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 200°C for debinding for 2 hours, the temperature is further increased to 400°C and maintained for 2 hours, and then the temperature is increased to 600°C and maintained for 8 hours to obtain a structured honeycomb catalytic carrier.
[0102] 2. Preparation of denitration catalyst based on the above catalytic carrier
[0103] (1) Take 25 parts of FeCu-ZSM-5 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 10 parts of silica sol, 2 parts of lactic acid, and 116 parts of deionized water, and mix them evenly to obtain a molecular sieve-based coating slurry.
[0104] (2) Weigh the structured honeycomb catalyst carrier, record it as m1, m1 = 62.31 g, and immerse it completely in the coating slurry for 4 hours. After taking it out, blow it with compressed air (4 bar) until no liquid drops fall to ensure the honeycomb permeability, and then dry it at 100°C for 8 hours to obtain sample A.
[0105] (3) Sample A was completely immersed in the coating slurry for 4 hours. After being taken out, it was purged with compressed air (4 bar) until no liquid droplets fell to ensure the honeycomb permeability. It was then dried at 100° C. for 8 hours to obtain sample B.
[0106] The sample was weighed and recorded as m2, m2 = 68.56 g. According to the load formula, L = (m2-m1) / m1×100%, L = 10.03%.
[0107] (4) Sample B was placed in a muffle furnace and heated to 600° C. for calcination for 5 h at a heating rate of 2° C. / min to obtain a highly loaded molecular sieve-based coated honeycomb monolithic denitrification catalyst.
[0108] The prepared high-load molecular sieve-based coated honeycomb monolithic denitrification catalyst was placed in the monolithic catalyst evaluation device to simulate the flue gas components N2, H2O, NO, NH3, and O2 for evaluation, maintaining the air velocity at 5000h -1 , [NO] = [NH3] = 500ppm, [O2] = 5%, H2O = 5%, respectively detect the NO concentration at the inlet and outlet, calculate the denitration efficiency of the catalyst, and the activity evaluation results are shown in Figure 1 .
[0109] The activity comparison results of Example 1 (addition of structure-making agent) and Example 4 (no addition of structure-making agent) are as follows: Figure 1 As shown. Figure 1 It can be seen that after adding the structure-making agent, the overall catalyst activity is significantly improved.
Claims
1. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier, characterized in that: The following steps are involved: (1) Taking natural silicon-aluminum mineral as the main body, adding a structure-making agent and an auxiliary agent, and mixing to obtain a uniform powder; adding wet material, kneading, slurrying, aging, extrusion molding, and pre-drying to obtain a clay-based honeycomb monolithic denitrification catalytic carrier; The structure-making agent is a water-soluble polymer bundle fiber; (2) soaking the above catalyst support in an alkali solution for etching: the pH of the alkali solution is 8 to 13, the temperature is 20 to 90° C., and the soaking time is 2 to 4 hours; (3) Performing a structured water-soluble treatment on the catalyst carrier: soaking the catalyst carrier in water at 20 to 90° C. for 0.5 to 2.0 h, and then rinsing it with water at 20 to 90° C. for 2 to 3 times; (4) Drying and calcining the catalyst carrier to obtain a structured clay-based honeycomb catalyst carrier.
2. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier according to claim 1, characterized in that: The water-soluble polymer bundle fibers are one or more of polyvinyl alcohol fibers, seaweed fibers, and carboxymethyl cellulose fibers.
3. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier according to claim 1, characterized in that: The auxiliary agents are organic binders, extrusion aids, pore formers and structure reinforcing agents, and the wet materials are inorganic binders, organic acids, inorganic acids, moisturizers and water.
4. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier according to claim 3, characterized in that: The organic binder is one or more of sodium carboxymethyl cellulose, sodium hydroxypropyl cellulose, polyethylene glycol, sodium polyacrylate, polyethylene oxide, and phenolic resin; the extrusion aid is one or more of starch, sesbania powder, ethanolamine, and sodium stearate; the pore-forming agent is one or more of straw, rice husk, sawdust, wood chips, and bamboo chips; the structural reinforcing agent is glass fiber; the inorganic binder is one or more of silica sol, water glass, pseudo-boehmite, and aluminum sol; the organic acid is one or more of citric acid, tartaric acid, malic acid, oxalic acid, and lactic acid; the inorganic acid is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, carbonic acid, and boric acid; the moisturizing agent is one or more of glycerin, tung oil, and peanut oil.
5. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier according to claim 3, characterized in that: The mass ratio of each raw material added is: natural silica-alumina mineral: organic binder: extrusion aid: structure enhancer: structure manufacturing agent: pore former: inorganic binder: organic acid: inorganic acid: humectant: water = 45-100: 1-5: 1-8: 1-5: 10-50: 1-15: 3-8: 1-5: 1-5: 3-10: 10-30.
6. A method for increasing the loading capacity of a clay-based honeycomb catalytic carrier according to claim 1, characterized in that: The drying method described in step (4) is temperature and humidity coordinated cross control, the temperature is 25-100° C., and the humidity is 5%-80%; The calcination method is: the initial temperature is greater than 80°C, then the temperature is increased at a rate of 0.5-2°C / min, and when the temperature reaches 180-400°C, the binder is removed for 2 hours, and then the temperature is continued to be increased to 550-800°C and calcined for 6-8 hours.
7. A clay-based honeycomb catalytic carrier obtained according to the preparation method according to any one of claims 1 to 6.
8. A method for preparing a highly loaded molecular sieve-based coated honeycomb monolithic denitration catalyst based on the clay-based honeycomb catalytic carrier according to claim 7, characterized in that: The following steps are involved: a) mixing molecular sieve, organic binder, inorganic binder, acid and water in a mass ratio of 10-30:0-10:0-10:3-10:50-90 to obtain a molecular sieve-based coating slurry; b) completely immersing the clay-based honeycomb catalyst carrier in the molecular sieve-based coating slurry for 4 to 8 hours, taking it out and drying it, immersing it in the molecular sieve-based coating slurry again for 4 to 8 hours, taking it out and drying it to obtain a primary product; c) calcining the primary product at 500-600° C. to obtain a highly loaded molecular sieve-based coated honeycomb monolithic denitration catalyst.
9. The method for preparing a high-load molecular sieve-based coated honeycomb monolithic denitration catalyst according to claim 8, characterized in that: The molecular sieve described in step a) is one or more of ZSM-5 molecular sieve, ZSM-35 molecular sieve, SSZ-13 molecular sieve, SSZ-39 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-47 molecular sieve, Y-type molecular sieve, Beta molecular sieve, KFI type molecular sieve, and mordenite, and the molar ratio of silicon dioxide to aluminum oxide of the molecular sieve is 2 to 300:1; the metal element contained in the molecular sieve is one or more of iron, copper, manganese, cerium, lanthanum, rhodium, ruthenium, palladium, and osmium, and the content of the metal element is 0.1 to 10.0wt%.
10. The method for preparing a high-load molecular sieve-based coated honeycomb monolithic denitration catalyst according to claim 8, characterized in that: The organic binder in step a) is one or more of sodium carboxymethyl cellulose, polyethylene glycol, polyethylene oxide, sodium polyacrylate, and polyimide resin; the inorganic binder is silica sol or aluminum sol; and the acid is one or more of lactic acid, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, carbonic acid, and boric acid.
Citation Information
Patent Citations
Method for manufacture of honeycomb catalyst
CA1194850A
Preparation method of honeycomb carrier catalyst for molecular sieve denitration
CN104353485A
Catalyst for treating wastewater as well as preparation method and application of catalyst
CN113117739A
Extrusion type honeycomb molecular sieve catalyst for simultaneous denitration and CO removal as well as preparation method and application of extrusion type honeycomb molecular sieve catalyst
CN116265112A
Cited By
Wear-resistant attapulgite honeycomb material with self-cleaning function as well as preparation method and application of wear-resistant attapulgite honeycomb material
CN120155175A
Wear-resistant attapulgite honeycomb material with self-cleaning function, preparation method and application thereof
CN120155175B
Honeycomb type hydrolysis catalyst suitable for fine desulfurization of coal gas and preparation method of honeycomb type hydrolysis catalyst
CN120790129A
